Effectiveness of radiotherapy for metastatic spinal cord compression in patients with short life expectancy - Giraldo, Alexandra (Rep Pract Oncol Radiother, 2017)
AIM: To analyze the effect of radiotherapy (RT) in patients with metastatic spinal cord compression (MSCC) and poor prognosis in our center. BACKGROUND: RT is an effective treatment for MSCC. MATERIALS AND METHODS: Prospective evaluation on patients with MSCC and limited survival (according to Rades’ scale), and treated with single-dose 8 Gy RT (February 2013–August 2014). Pain, ambulatory status and sphincter control were recorded. Pain relief was evaluated following the International Bone Metastases Consensus Working Party Guidelines. Ambulatory status was evaluated with Frankel's scale. Spinal fracture and instability were recorded. Health aspects were evaluated via a short survey and measuring the time spent on RT. RESULTS: 35 patients were included. 51% had unfavorable histologies; 60% bone fracture and 17% spinal instability. Median Karnofsky score was 60; 100% were on high doses of opioids. Median survival was 1.5 months. 49% had a partial pain response at 2 weeks post-radiation, and 47% at one month. Significant reductions in pain intensity were present at 2 weeks (Visual analog scale, VAS score, from 8 ± 1.5 to 5 ± 1.9). Negligible effects were observed on motor and bladder function, along with side effects. KPS score was maintained during follow-up. 80% of patients spent ≤5% of their remaining lifetime on RT. A survey comparison between clinical judgment and the results according to treatment decision consider that these patients merit treatment evaluation. CONCLUSIONS: A moderate pain response tailored to life expectancy can be obtained in patients treated with radiation. 8-Gy single-dose is an option for patients with limited survival.